iEVENT INFORMATION : MEDIA INFORMASI DAN PUBLIKASI JADWAL KEGIATAN KAMPUS - Ary Budi Warsito; Untung Rahardja; Aghnia Sabila (Universitas Raharja, 2013)
Liabilities to document an event in the world of education is the provision that created in order to improve the quality and the quality of education in Indonesia. As well as reference material that can be used as an ingredient to evaluate a wide range of events that have been implemented. So, to support this Perguruan Tinggi Raharja which is one institution that engages in computer science is always innovative and creative in order to solve these problems, by applying an iLearning learning system, based on 4B (Belajar, Bekerja, Bermain, and Berdoa) by using a new technology device, iPad. In iLearning, learning system of teaching and learning process requires the applications contained in the iPad. Based on the results of surveys and studies have been performed, have not all applications support are included in the iPad, especially applications that can support the process of making and publication about events that are held, so it created one of the supporting applications as one of the iEvent Information applications that support system, especially in terms of learning iLearning publicize campus events that have been held or to be carried out.